EFEKTIVITAS PENGGUNAAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS KETERAMPILAN PROSES SAINS (KPS) TERHADAPHASIL BELAJAR SISWA DI SMA NEGERI 1 SEBATIK - Mariani Mariani; Fitri Wijarini; Nursia Nursia (Department of Biology Education, Universitas Borneo Tarakan, 2025)
The purpose of this study was to evaluate the impact of employing Student Work Sheets based on scientific method skills on the learning outcomes of students at SMA Negeri 1 Sebatik. The quantitative descriptive techniques used in this study. All of the students in class XI PSP SMA Negeri 1 Sebatik made up the study's population. With a total sample size of 36 students, the sampling technique used purposive sampling. Using a multiple-choice test with 30 questions and 12 indicators, including using as many senses as possible, looking for differences and similarities, contrasting characteristics, concluding, stating what happened in situations that have not been observed, seeking explanations, formulating questions based on hypotheses, choosing the tools and materials/resources to be used, and choosing what would be implemented in the form of what, science process skills were measured. The N-Gain Test and the Paired Sample T- test were used to examine the research findings. The paired sample t-test showed a tvalue of -18.168 with a significance level of less than 0.05, or (0.001), meaning 0.001 < 0.05, signifying that H0 was rejected and H1 was accepted. The findings of the N-Gain Test value were 0.7705 with high criteria. The use of Student Work Sheets (LKS) based on Science Process Skills (KPS) was effective on learning outcomes students at SMA Negeri 1 Sebatik as shown by the significant difference between the average pretest and posttest scores and the achievement of class mastery learning outcomes reached a score of 75% with a KKM (minimun score standart) score of 72.